2005
DOI: 10.1038/sj.ijo.0802996
|View full text |Cite
|
Sign up to set email alerts
|

Early anthropometric measures and reproductive factors as predictors of body mass index and obesity among older women

Abstract: OBJECTIVE:To examine whether early anthropometric measures and reproductive factors were associated with body mass index (BMI), overweight, and obesity. DESIGN: Cross-sectional, observational study. SUBJECTS: In all, 18 109 healthy women who participated in the Swedish Mammography Cohort aged 49-83 y. MEASUREMENTS: Early anthropometric (birthweight and body shape at age 10 y) and reproductive (age at menarche, age at the birth of the first child, and parity) variables were our predictors and current BMI, overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 53 publications
1
28
1
1
Order By: Relevance
“…Previous studies have shown that the association between birth weight and obesity later in life apparently follows a U-shaped curve [8]. However, due to the continuous increase, in the last two decades, of mean birth weight in several countries worldwide [9,10], it is expected that higher birth weight will play a more important role as a risk factor for further obesity [5,11,12] than low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the association between birth weight and obesity later in life apparently follows a U-shaped curve [8]. However, due to the continuous increase, in the last two decades, of mean birth weight in several countries worldwide [9,10], it is expected that higher birth weight will play a more important role as a risk factor for further obesity [5,11,12] than low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…9, 10 In the longer term, after a woman's reproductive years are over, some investigators have also found that various measures of adiposity are increased the more children women had, although the evidence is somewhat inconsistent. 11, 12, 13, 14, 15, 16 To our knowledge only two small studies have looked at the association between breastfeeding history and postmenopausal adiposity and their findings suggest a possible reduction in BMI associated with breastfeeding. 17, 18 Women's BMI is known to be related to socioeconomic factors, smoking and physical activity, and these factors are associated with reproductive history.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have observed that childhood obesity may accelerate age at menarche, especially in those of low birth weight (5), (13), (44), (45), and early age at menarche is a known risk factor for breast cancer development. In our study we observed that women of birth weight < 3530 g tended to have an earlier age at menarche than those in the highest birth weight tertile, " 3530 g. A Swedish study suggested that girls who at birth were relatively small for gestational age had higher childhood growth velocities than other girls (46).…”
mentioning
confidence: 99%